Analisis Hukum Terhadap Perkawinan Beda Agama Dalam Persektif Hukum Islam - Febrianti Hutagalung; Rizal Sanusi Hasibuan; Sulastri Krisdayanti Sinambela; Sri Hadiningrum (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
An interfaith marriage is a marriage between followers of different religions, but because Indonesian society has various religions, they still adhere to their respective religions. Articles 40(c) and 44 of the KHI provide an explanation that non-Muslim women may not marry men. Muslim men, whatever their religion. The research method used by the author is a normative juridical legal research method. Ronnie Hanitiho explains: